Phenomenological aspects of the cognitive rumination construct - Meyer,Leonardo Fernandez (2015)
Objective: To evaluate the importance of phenomenological aspects of the cognitive rumination (CR) construct in current empirical psychiatric research.Method: We searched SciELO, Scopus, ScienceDirect, MEDLINE, OneFile (GALE), SpringerLink, Cambridge Journals and Web of Science between February and March of 2014 for studies whose title and topic included the following keywords: cognitive rumination; rumination response scale; and self-reflection. The inclusion criteria were: empirical clinical study; CR as the main object of investigation; and study that included a conceptual definition of CR. The studies selected were published in English in biomedical journals in the last 10 years. Our phenomenological analysis was based on Karl Jaspers' General Psychopathology.Results: Most current empirical studies adopt phenomenological cognitive elements in conceptual definitions. However, these elements do not seem to be carefully examined and are indistinctly understood as objective empirical factors that may be measured, which may contribute to misunderstandings about CR, erroneous interpretations of results and problematic theoretical models.Conclusion: Empirical studies fail when evaluating phenomenological aspects of the cognitive elements of the CR construct. Psychopathology and phenomenology may help define the characteristics of CR elements and may contribute to their understanding and hierarchical organization as a construct. A review of the psychopathology principles established by Jasper may clarify some of these issues.